High-throughput measurements of interdiffusivities in fcc Co–Ni–Ta alloys at 1373K and 1473K. (March 2023) - Wu, Xue-Ting; Xia, Cheng-Hui; Xia, Shi-Lin; Lu, You-Ming; Lu, Xiao-Gang
Abstract: The composition-dependent interdiffusivities in the fcc Co–Ni–Ta alloys at 1373 K and 1473 K were deduced by using our newly developed numerical inverse scheme that combines two-dimensional (2D) simulations with diffusion triple experiments. This approach largely reduced the experimental efforts by analyzing only one single-phase diffusion triple at each temperature yet covering a much wider composition range than diffusion couples. The reliability of the high-throughput results was firstly verified by reproducing the experimental 2D composition profiles in each triple. In order to further validate the deduced interdiffusivities, several traditional one-dimensional (1D) diffusion couples were also devised, and the widely recognized Sauer-Freise method and Whittle-Green method were then employed to calculate the interdiffusivities for the binaries and at the intersection points within the ternary composition range, respectively. The interdiffusivities extracted from the inverse scheme agree well with those from the traditional approaches, which strongly proves the applicability of the present new scheme. Besides, the constructed main interdiffusivity planes at 1373 K and 1473 K provide an overview of the diffusion behavior in the fcc Co–Ni–Ta system and promote further kinetic studies. Highlights: The present inverse scheme deduces interdiffusivities covering two-dimensional (2D) composition region. Diffusion triple technique requires much less experimental efforts than diffusion couple method. Deduced interdiffusivities fairly consistent with those calculated from traditional methods.